Regulating the regulator: nitric oxide control of post-translational modifications - Gupta, Kapuganti Jagadis; Kolbert, Zsuzsanna; Durner, Jorg; Lindermayr, Christian; Corpas, Francisco J; Brouquisse, Renaud; Barroso, Juan B; Umbreen, Saima; Palma, José M; Hancock, John T; Petrivalsky, Marek; Wendehenne, David; et al. (The New phytologist, 2020)
Nitric oxide (NO) is perfectly suited for the role of a redox signalling molecule. A key route for NO bioactivity occurs via protein S-nitrosation, and involves the addition of a NO moiety to a protein cysteine (Cys) thiol (-SH) to form an S-nitrosothiol (SNO). This process is thought to underpin a myriad of cellular processes in plants that are linked to development, environmental responses and immune function. Here we collate emerging evidence showing that NO bioactivity regulates a growing number of diverse post-translational modifications including SUMOylation, phosphorylation, persulfidation and acetylation. We provide examples of how NO orchestrates these processes to mediate plant adaptation to a variety of cellular cues.
Keywords: Plants; reactive nitrogen species (RNS); oxidace-redukce; reactive oxygen species (ROS); oxid dusnatý; S-Nitrosothiols; Nitric Oxide; S-nitrosation; Protein Processing, Post-Translational; posttranslační úpravy proteinů; nitrosace; persulfidation; Nitrosation; phosphorylation; SUMOylation; Oxidation-Reduction; nitric oxide (NO); S-nitrosothioly; rostliny; S-nitrosylation